(untitled) (Clinics, 2013)
OBJECTIVE: To study the prevalence of potentially life-threatening maternal conditions and near miss in Brazil according to maternal age. METHODS: A secondary analysis of the 2006 Brazilian demographic health survey database using a validated questionnaire to evaluate maternal morbidity with a focus on age extremes. The study included 5,025 women with at least 1 live birth in the 5-year reference period preceding their interviews. Three age range periods were used: 15-19 years (younger age), 20-34 years (control), and 35-49 years (advanced maternal age). According to a pragmatic definition, any woman reporting eclampsia, hysterectomy, blood transfusion, or admission to the intensive care unit during her pregnancy/childbirth was considered a near-miss case. The associations between age and severe maternal morbidity were further assessed. RESULTS: For the 6,833 reported pregnancies, 73.7% of the women were 20-34 years old, 17.9% were of advanced maternal age, and only 8.4% were of younger age. More than 22% of the women had at least one of the complications appraised, and blood transfusion, which was more prevalent among the controls, was the only variable with a significant difference among the age groups. The overall rate of maternal near miss was 21.1 per 1000 live births. There was a trend of higher maternal near miss with increasing age. The only significant risk factor identified for maternal near miss was a lower literacy level among older women. CONCLUSIONS: There is a trend towards worse results with increasing age. The investigation of the determinants of maternal near miss at the community level using an innovative approach through a demographic health survey is an example suggested for under-resourced settings.